2021
DOI: 10.3390/mi12121547
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Solid-Phase Oxidant Action in Tribochemical Mechanical Polishing of SiC Single Crystal Substrate

Abstract: Na2CO3—1.5 H2O2, KClO3, KMnO4, KIO3, and NaOH were selected for dry polishing tests with a 6H-SiC single crystal substrate on a polyurethane polishing pad. The research results showed that all the solid-phase oxidants, except NaOH, could decompose to produce oxygen under the frictional action. After polishing with the five solid-phase oxidants, oxygen was found on the surface of SiC, indicating that all five solid-phase oxidants can have complex tribochemical reactions with SiC. Their reaction products are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, surface roughness (Sa) also increased around two fold for the test group, indicating the effect of non-uniform abrasion [ 10 ]. In 2021, Qi et al investigated five solid-phase abrasive oxidants, including Na 2 CO 3 -1.5H 2 O 2 , KIO 3 , KClO 3 , KMnO 4 and NaOH, for Tribo-CMP on 6H-SiC [ 11 ]. The SiC surface can be oxidized by oxygen generated from the decomposition of oxidants, along with friction-induced heat and water in the slurry formulation or ambient air.…”
Section: Various Sic Cmp Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surface roughness (Sa) also increased around two fold for the test group, indicating the effect of non-uniform abrasion [ 10 ]. In 2021, Qi et al investigated five solid-phase abrasive oxidants, including Na 2 CO 3 -1.5H 2 O 2 , KIO 3 , KClO 3 , KMnO 4 and NaOH, for Tribo-CMP on 6H-SiC [ 11 ]. The SiC surface can be oxidized by oxygen generated from the decomposition of oxidants, along with friction-induced heat and water in the slurry formulation or ambient air.…”
Section: Various Sic Cmp Technologiesmentioning
confidence: 99%
“…A MRR of more than 1 µm h −1 can be consistently obtained for all five oxidants, but the resulting surface roughness was unsatisfactory. Meanwhile, obvious surface scratches and pits can be found under SEM inspection [ 11 ]. In addition to the solid-phase abrasive oxidants described above, in 2021, Ni et al applied synthetic SiO 2 /CeO 2 abrasives for CMP on the Si-face surface, under the conditions of polishing pressure = 3.5 psi and rotation speed = 90 rpm with a polyurethane pad [ 12 ].…”
Section: Various Sic Cmp Technologiesmentioning
confidence: 99%
“…Tribochemical mechanical polishing is a new technology in the field of Ultraprecision machining [20,21]. It uses abrasives and chemical additives to conduct tribochemical reactions on the polishing pad, change the surface structure of the workpiece through chemical action, and effectively remove the workpiece materials through mechanical action.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of good surface flatness and fewer scratches on the workpiece obtained by this method, it has attracted extensive the attention of many scholars. Qi et al [28] used five different solid-phase oxidants for the tribochemical mechanical polishing of silicon carbide and found that oxygen was generated on the surface of silicon carbide, and the experiments showed that all five oxidants could have a tribochemical reaction with silicon carbide, and the oxygen generated by the tribochemical reaction between the solid-phase oxidants and silicon carbide could oxidize the surface of silicon carbide and generate a shear film that could be easily removed. Ootani et al [29] mainly studied the friction properties of Si3N4 and SiC in water, and explored their mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to eliminate microcracks and improve surface quality, chemical mechanical polishing (CMP), which is an effective method to obtain smooth and damage-free wafers through chemical reactions, is employed; however, the material removal rate (MRR) of SiC wafers is significantly low because of the high hardness and stable chemical properties of the SiC materials. Therefore, the production of high-performance SiC wafers is limited because CMP using acid-base chemical reagents is expensive and polluting [20][21][22].…”
Section: Introductionmentioning
confidence: 99%